Microstructure, high-temperature deformability and oxidation resistance of a Ti5Si3-containing multiphase MoSiBTiC alloy. (November 2017) - Zhao, Mi; Nakayama, Shunichi; Hatakeyama, Tomotaka; Nakamura, Junya; Yoshimi, Kyosuke
Abstract: A Ti5 Si3 -containing multiphase MoSiBTiC alloy with a composition of 38Mo–30Ti–17Si–10C–5B (at.%) was designed and produced by arc-melting. The alloy was composed of five phases—Mo solid solution (Moss ), Mo3 Si, Mo5 SiB2 (T2 ), Ti5 Si3 and TiC—and consistently has good thermal stability at least up to 1700 °C. The density of the alloy was ∼7.0 g/cm 3, which is considerably smaller than that of Ni-base superalloys. Microstructure was carefully examined and microstructural anisotropy was confirmed. The anisotropy was considered to be generated by thermal gradient during the solidification process. Microcracking was remarkable across the primary Ti5 Si3 phase, which was caused by thermal expansion anisotropy of the Ti5 Si3 phase. High-temperature deformability was examined by high-temperature compression tests at 1500 °C. Two kinds of loading axes were chosen for the compression tests with respect to the microstructural anisotropy. The alloy exhibited a peak stress of 450–550 MPa, followed by good deformability at the testing temperature. Microstructure refinement and reduction in microcrack density were observed after hot working. Oxidation tests were conducted on the alloy at 1100 °C and 1300 °C for 24 h. The oxidation curves demonstrated that rapid mass loss finished within several minutes. After that, the mass loss began to slow down and then the specimens' mass decreased almost linearly with increasing testing time. Cross-section observation indicated that oxygen propagated through Moss, whereas T2 and Ti5 Si3 phases acted as barriers against oxygen attack during the tests. In addition, it was found that the alloy gained better oxidation resistance after high-temperature deformation, suggesting a positive effect of phase refinement on its high-temperature oxidation resistance. Highlights: Microstructural anisotropy was found in the Ti5 Si3 -containing MoSiBTiC alloy. This alloy has good deformability at 1500 °C. Microstructure optimization can be achieved through hot working. Oxidation resistance of this alloy can be improved by microstructure refinement.